If f : R → R, g : R → R are defined by

Question:

If $f: R \rightarrow R, g: R \rightarrow R$ are defined by $f(x)=5 x-3, g(x)=x^{2}+3$, then $\left(g \circ f^{-1}\right)(3)=$

Solution:

Given: $f(x)=5 x-3$ and $g(x)=x^{2}+3$

$f(x)=5 x-3$

$\Rightarrow y=5 x-3$

$\Rightarrow 5 x=y+3$

$\Rightarrow x=\frac{y+3}{5}$

Thus, $f^{-1}(y)=\frac{y+3}{5}$.

Now,

$g o f^{-1}(3)=g\left(f^{-1}(3)\right)$

$=g\left(\frac{3+3}{5}\right)$

$=g\left(\frac{6}{5}\right)$

$=\left(\frac{6}{5}\right)^{2}+3$

$=\frac{36}{25}+3$

$=\frac{36+75}{25}$

$=\frac{111}{25}$

Hence, gof $^{-1}(3)=\frac{111}{25}$.

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now